ANALISIS RENCANA PELAKSANAAN PEMBELAJARAN TEMATIK MENGGUNAKAN MODEL EXAMPLE NON-EXAMPLE DI KELAS V SEKOLAH DASAR - Liza Khasanah Sudrajat; Siti Halidjah; Dyoty Auliya Vilda Ghasya (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to describe the components and the accuracy of the steps in the thematic learning implementation plan using the example non-example model in class V Elementary School 03 Sungai Raya, Kuburaya Regency. Based on the research results, it can be concluded that:(1) In the first lesson plan the teacher compiles the lesson plans components in a complete and systematic manner. On the step accuracy of the example non-example learning model the teacher arranges systematically, but there is a mismatch between the learning activities made with the third activity step (2) In the second lesson plan, the teacher compiles the lesson plan components systematically and coherently but incomplete in the assessment section. On the step accuracy of the example non-example learning model the teacher does not compile the lesson plan systematically and sequentially, but the steps of the activities are in accordance with the model used (3) In the third lesson plan, the teacher compiles the lesson plan components systematically and coherently but incomplete in the core activities and assessment section. On the step accuracy of the example non-example learning model, the teacher arranges systematically and accordingly, but the teacher does not describe the third step in the model.Keywords: Example Non-Example, Learning Implementation Plan Analysis